Intimacy as Inquiry: Collaborative Reading and Writing With Deleuze and Guattari. (December 2021) - Bittinger, Ryan; Clarke, David A. G.; Erb, Jess; Hauser, Holt; Wyatt, Jonathan
This article performs the becoming intimacy of a reading (and, later, writing) group who met once a month for 2 years to discuss Deleuze and Guattari's A Thousand Plateaus . Through this collaborative piece, we explore the question of intimacy as both a form of activism and a mode of inquiry. We ask, "Where is activism as we subvert the hierarchy of academia by meeting as an assemblage of differing perspectives and positions in the university?" Furthermore, we ask, "What does the intimacy that occurred, that is occurring, do for both inquiry and activism?." This article contains two sets of writing from our monthly meetings that we offered as performative conference texts. We contend that it is affect that brings our theorizing to life, and transfers it meaningfully between each other. We are affected by Deleuze and Guattari, by A Thousand Plateaus, and by how we form linkages with our lives to these bodies. Intimacy is what sustains and gives life to our collective inquiry, without which our affect might be more constrained. The complexity of the becoming of "intimacy as inquiry" becomes twofold, as it is not only a becoming of intimacy, love, and care for those in our assemblage but also a reterritorialization of the act of inquiry. Through the act of disrupting power structures in the group of "We 5, " the act of writing and presenting this work in an academic context pushes against the striated spaces that exist in the academy, that course through the milieu we occupy, and provides the means and necessity for reterritorializing the epistemic space. "Epistemic intimacy, " then, becomes a manifestation of engaging with the inquiry process and embodies an active resistance to the business transaction that the act of inquiry has become in the neoliberal development of the academy.